2004
DOI: 10.1002/ajmg.a.20691
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 14 rare marker chromosomes and derivatives by spectral karyotyping in prenatal and postnatal diagnosis

Abstract: Extra structurally abnormal chromosomes (ESACs) and cryptic rearrangements are often associated with mental retardation and phenotypic abnormalities. In some cases their characterisation, using standard cytogenetic techniques and fluorescence in situ hybridization (FISH), is difficult and time consuming, where a fast and accurate identification is essential, especially when such chromosomal aberrations are found in prenatal diagnosis. A recent molecular technique, spectral karyotyping (SKY), based on the spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Therefore more sophisticated approaches have been developed. The application of micro-FISH (Anderlid et al 2001;Engelen et al 2003;Trimborn et al 2005) and multicolor karyotyping technologies, such as multiplex-FISH (M-FISH), including centromere-specific multicolor FISH (cenM-FISH; Nietzel et al 2001) or spectral karyotyping (SKY) (Guanciali-Franchi et al 2004) in analysis of marker chromosomes, was demonstrated in the literature. Taking into account that approximately 80% of all SMCs derive from acrocentric chromosomes, Langer et al (2001) described a new strategy for their rapid and detailed identification.…”
Section: Marker Chromosomesmentioning
confidence: 99%
“…Therefore more sophisticated approaches have been developed. The application of micro-FISH (Anderlid et al 2001;Engelen et al 2003;Trimborn et al 2005) and multicolor karyotyping technologies, such as multiplex-FISH (M-FISH), including centromere-specific multicolor FISH (cenM-FISH; Nietzel et al 2001) or spectral karyotyping (SKY) (Guanciali-Franchi et al 2004) in analysis of marker chromosomes, was demonstrated in the literature. Taking into account that approximately 80% of all SMCs derive from acrocentric chromosomes, Langer et al (2001) described a new strategy for their rapid and detailed identification.…”
Section: Marker Chromosomesmentioning
confidence: 99%
“…SKY analysis permitted the classification of marker chromosomes and chromosome rearrangements and the results were confirmed by using locus/gene-specific probes with FISH analysis (Haddad et al, 1998;Huang et al, 1998;Ning et al, 1999;Yaron et al, 2003;Guanciali-Franchi et al, 2004;Tabet et al, 2004). However, in two cases of small bisatellited chromosomes, SKY was noncontributory (Yaron et al, 2003).…”
Section: Applications Of Chromosome Analysis Using Sky In Clinical Gementioning
confidence: 93%
“…To our knowledge, prenatally ascertained de novo apparently balanced complex and multiple chromosomal rearrangements have been reported in 19 cases [3,9,15,16] . Here, we describe a new case of a de novo CCR de- tected prenatally by conventional cytogenetics and fluorescence in situ hybridization (FISH).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate identification of CCRs is a challenge to cytogeneticists, especially when they are found in prenatal diagnosis posing problems in counseling couples [3,9] . The application of molecular cytogenetics has greatly improved the accuracy of cytogenetic diagnosis and uncovered a number of cryptic aberrations in cases previously studied by conventional cytogenetics [8,[10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation